Unraveling the Molecular Signature of Extracellular Vesicles From Endometrial-Derived Mesenchymal Stem Cells: Potential Modulatory Effects and Therapeutic Applications - Marinaro, Federica; Gómez-Serrano, María; Jorge, Inmaculada; Silla-Castro, Juan Carlos; Vázquez, Jesús; Sánchez-Margallo, Francisco Miguel; Blázquez, Rebeca; López, Esther; Álvarez, Verónica; Casado, Javier G. (Frontiers in Bioengineering and Biotechnology, 2019)
Endometrial-derived Mesenchymal Stem Cells (endMSCs) are involved in the regeneration and remodeling of human endometrium, being considered one of the most promising candidates for stem cell-based therapies. Their therapeutic effects have been found to be mediated by extracellular vesicles (EV-endMSCs) with pro-angiogenic, anti-apoptotic, and immunomodulatory effects. Based on that, the main goal of this study was to characterize the proteome and microRNAome of these EV-endMSCs by proteomics and transcriptomics approaches. Additionally, we hypothesized that inflammatory priming of endMSCs may contribute to modify the therapeutic potential of these vesicles. High-throughput proteomics revealed that 617 proteins were functionally annotated as Extracellular exosome (GO:0070062), corresponding to the 70% of the EV-endMSC proteome. Bioinformatics analyses allowed us to identify that these proteins were involved in adaptive/innate immune response, complement activation, antigen processing/presentation, negative regulation of apoptosis, and different signaling pathways, among others. Of note, multiplexed quantitative proteomics and Systems Biology analyses showed that IFNγ priming significantly modulated the protein profile of these vesicles. As expected, proteins involved in antigen processing and presentation were significantly increased. Interestingly, immunomodulatory proteins such as CSF1, ERAP1, or PYCARD were modified. Finally, proteins involved in the negative regulation of the apoptotic process such as SOD2, TIMP1, and PLAUR were also differentially expressed. Regarding miRNAs expression profile in EV-endMSCs, Next-Generation Sequencing (NGS) showed that the preferred site of microRNAome targeting was the nucleus (n=371 microTargets), significantly affecting signal transduction (GO:0007165), cell proliferation (GO:0008283), and apoptotic processes (GO:0006915), among others. Interestingly, NGS analyses highlighted that several miRNAs, such as hsa-miR-150-5p or hsa-miR-196b-5p, were differentially expressed in IFNγ-primed EV-endMSCs. In summary, these results allowed us to understand the complexity of the molecular networks in EV-endMSCs and their potential effects on target cells. To our knowledge, this is the first comprehensive study based on proteomic, and genomic approaches to unravel the therapeutic potential of these extracellular vesicles.